2016
DOI: 10.15740/has/ijfci/7.1/19-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature on the activity of entomopathogenic nematodes

Abstract: The present study was investigated the effect of low temperature on the activity of the entomopathogenic nematodes, Heterorhabditis indica and Steinernema glaseri. The effects of low temperature at 5 0 to 25 0 C were tested under BOD conditions. The survival and infectivity of entomopathogenic nematodes in insect host were studied. Survival of H. indica was significantly greater at the lowest temperature of 10 0 C conversely survival of S. glaseri was significantly greater at a temperature of 5 0 and 10 0 C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Yadav (2016) also reported that the storage of the IJs of the same EPN species at a lower temperature (5 °C) led to a high decrease in the survival of IJs and S. glaseri was the only EPN species that survived after 4 months of storage at 5 °C. Similar to our findings, Sharmila and Subramanian (2016) reported 50 and 48% survival rates in the IJs of H. indica that were stored in deionized water for three months at 10 and 25 °C, respectively. However, in the current study, all tested EPN species survived for 6 months albeit with a notable decrease in survival rates of IJs.…”
Section: Pathogenicity Of Infective Juvenilessupporting
confidence: 91%
“…Yadav (2016) also reported that the storage of the IJs of the same EPN species at a lower temperature (5 °C) led to a high decrease in the survival of IJs and S. glaseri was the only EPN species that survived after 4 months of storage at 5 °C. Similar to our findings, Sharmila and Subramanian (2016) reported 50 and 48% survival rates in the IJs of H. indica that were stored in deionized water for three months at 10 and 25 °C, respectively. However, in the current study, all tested EPN species survived for 6 months albeit with a notable decrease in survival rates of IJs.…”
Section: Pathogenicity Of Infective Juvenilessupporting
confidence: 91%
“…In agricultural use, it is not uncommon for EPNs to endure extended storage times. It has been previously demonstrated that storage temperature may affect both the survival and infectivity of EPNs [ 23 , 24 ]. Since previous work had demonstrated that the response of some EPNs to prenol were affected by moderate storage times [ 5 , 18 ], we wondered how longer time periods of storage/aging would impact the IJs’ behavior.…”
Section: Resultsmentioning
confidence: 99%